2009
DOI: 10.1007/s10142-009-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent gene regulatory networks of the heart rhythm

Abstract: Expression level, control, and intercoordination of 66 selected heart rhythm determinant (HRD) genes were compared in atria and ventricles of four male and four female adult mice. We found that genes encoding various adrenergic receptors, ankyrins, ion channels and transporters, connexins, cadherins, plakophilins, and other components of the intercalated discs form a complex network that is chamber dependent and differs between the two sexes. In addition, most HRD genes in atria had higher expression in males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 82 publications
1
19
0
Order By: Relevance
“…Moreover, such pervasive transcriptomic changes provide the expectation that phenotype resulting from knockdown of Cx43 might be highly variable with regard to strain, age or sex or other environmental conditions. In support of this hypothesis, we have found major sex dependent differences in gene expression changes in heart ventricles and atria (Iacobas et al, 2010), and it was reported that transgenic deletion of the astrocyte-specific gap junction gene Gja1 (encoding Cx43) in a GFAP-targeted strategy led to markedly different morphological and behavioral phenotypes in two different mouse strains (Wiencken-Barger et al, 2007). Moreover, these results were reminiscent of the profound destruction of the midbrain-hindbrain region obtained when the mitogen Wnt1 was deleted (Melloy et al, 2005); strikingly, when the authors crossed Wnt-1 heterozygotes into a Cx43 overexpressing mouse line, the expression of anatomically correct cerebellum was rescued in a substantial percentage of offspring (Melloy et al, 2005).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, such pervasive transcriptomic changes provide the expectation that phenotype resulting from knockdown of Cx43 might be highly variable with regard to strain, age or sex or other environmental conditions. In support of this hypothesis, we have found major sex dependent differences in gene expression changes in heart ventricles and atria (Iacobas et al, 2010), and it was reported that transgenic deletion of the astrocyte-specific gap junction gene Gja1 (encoding Cx43) in a GFAP-targeted strategy led to markedly different morphological and behavioral phenotypes in two different mouse strains (Wiencken-Barger et al, 2007). Moreover, these results were reminiscent of the profound destruction of the midbrain-hindbrain region obtained when the mitogen Wnt1 was deleted (Melloy et al, 2005); strikingly, when the authors crossed Wnt-1 heterozygotes into a Cx43 overexpressing mouse line, the expression of anatomically correct cerebellum was rescued in a substantial percentage of offspring (Melloy et al, 2005).…”
Section: Discussionsupporting
confidence: 55%
“…For RNA extraction and hybridization, 20 μg total RNA extracted in Trizol from brains of each of the 32 mice (4 per condition) was reverse transcribed in the presence of fluorescent Alexa Fluor®_647 and Alexa Fluor®_555-aha-dUTPs (Invitrogen, CA) to obtain labeled cDNAs Red- and green-labeled samples of biological replicas were then co-hybridized (“multiple yellow” strategy, Iacobas et al 2010) overnight at 50°C with mouse MO36k oligonucleotide arrays printed by Duke University Microarray Facility with Operon Mouse Oligo Set, version 4.0 (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GPL8928). After washing (0.1% SDS and 1% SSC) to remove the non-hybridized cDNA, each array was scanned with a GenePix 4000B scanner (MDS, Toronto, Canada) and images were primarily analyzed with GenePixPro 6.0 (Axon Instruments, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In the ventricles, there is also a slight male bias in overall relative transcript expression levels (Figure 3C), although in contrast with the atria the pattern emerges in nonfailing hearts, as opposed to failing LV. Interestingly, previous studies in wild-type mouse hearts demonstrated a similar male gender bias in overall atrial gene expression [36].…”
Section: Resultsmentioning
confidence: 57%
“…Information on cardiac genes consists of several databases that are difficult to combine with traditional gene regulatory network (GRN) models as they address heart evolution, cardiac development, function, cardiac conduction systems and cardiac pathology separately and therefore are based on different heuristics. As an example, well above one hundred heart rhythm determinant genes that are sex-dependent have been identified [1], with many more associated with development, function and pathology. Restricting GRN studies to possible disease biomarkers disregards genes associated with controlling expression of downstream genes and interconnection of gene regulatory pathways.…”
Section: Introductionmentioning
confidence: 99%